Some New Ostrowski type inequalities on time scales for functions of two independent variables. Issue 2 (17th February 2017) - Meftah, B.; Khaled, Boukerrioua
Abstract: By making use of the kernel given in [11], some new Ostrowski-type inequalities on time scales for double integrals are established. The results obtained here can be used in the estimation of the error.